The impact of curriculum on nursing students' attitudes, perceptions and preparedness to work in primary health care: An integrative review. (August 2019) - Calma, Kaara Ray B.; Halcomb, Elizabeth; Stephens, Moira
Abstract: Background: The ageing population and growing burden of chronic disease has increased demands for primary health care services, necessitating growth of this nursing workforce. Studies have explored strategies in retaining nurses, employment conditions in primary health care, and transitioning of acute care nurses to primary health care employment. Few studies have explored how undergraduate nursing students perceive and are prepared to work in this sector. Aim: This review synthesises evidence on the impact of undergraduate curriculum on nursing students' attitudes, perceptions and preparedness to work in primary health care. Design: An integrative literature review guided the synthesis of evidence. Data sources: Scopus, ScienceDirect, CINAHL and MEDLINE were searched for relevant studies published between 2008 and 2018. Review methods: 491 studies were identified from the database searches. Following the removal of duplicates, review of abstracts and keywords against the inclusion and exclusion criteria, 39 papers were subjected to full-text review. Twelve papers, including one thesis, met the inclusion criteria. Using an appraisal system, no paper was excluded based on methodological quality. Results: Three themes were identified, namely: impact of curricula; knowledge and attitudes to primary health care; and students' intention to work in primary health care. The preparation of undergraduate nursing students to work in this area is inconsistent as curricula remain acute-care focussed. Negative perceptions about the primary health care nursing role impact intentions of nursing students to work in primary health care. Conclusion: This review highlights a need to implement strategies to improve the understanding of undergraduate nurses around the primary health care nursing role. In particular, providing students with skills, knowledge and an understanding of working in this area through curriculum content and structure may provide undergraduates with the desire and confidence to seek employment in primary health care following graduation.